Unforeseen Territories, Foreigners’ Rights and Infralegality. The Case of the European Roma Citizens in Naples - D'Andrea, Margherita (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2025)
This study hypothesizes that, within the domains of immigration law and the free movement and residence of EU citizens of Roma ethnicity, the gap between the formal validity of legal norms and their practical effectiveness gives rise to a weakened and unstable form of legality. I conceptualize this grey zone as infralegal. Drawing on socio-legal approaches, the analysis examines how legality is produced, negotiated, and at times undermined through everyday administrative practices. The investigation focuses on the protection of the rights of European Roma citizens and was carried out within Justrom2, a legal clinic established under the Joint Programme of the Council of Europe and the European Commission. It also incorporates findings from a study by the Italian Association for Juridical Studies on Immigration (ASGI) concerning the obstacles foreign nationals face in accessing immigration offices. The research shows how configurations of knowledge and power—embedded both in normative frameworks and in their absences—contribute to the production of discriminatory representations (Ferrajoli, 2017). These representations shape routine institutional interactions and thereby erode the rights of groups already positioned at the margins of citizenship. Furthermore, the recent proliferation of restrictive legislative reforms affecting the protection of foreigners, particularly asylum seekers, increases the risk of expanding such ambiguous administrative practices. These dynamics call not only for judicial scrutiny where unlawfulness emerges, but also for a systemic socio-legal analysis capable of addressing how institutional arrangements, bureaucratic routines, and discretionary interpretation collectively redefine the boundaries of legality.